Analysis of Influencing Factors Completion of Thesis on Students of The Study Program Building Engineering Education at the Time of the Covid-19 Pandemic - Irvan Hidayatullah; Dedy Suryadi; Siti Nurasiyah (Universitas Pendidikan Indonesia, 2021)
Factors can influence students in completing theirthesisamong others, factors from within students, from theenvironment and many morefactors that influence it. As weknow the current environmental conditionsis experiencingthe Covid-19 (Corona Virus Diseases-19) pandemic that hashitvarious countries around the world. This situationbecomes a new problem for final semester students whoare contracting thesis courses because they are incarry outthe process online or online. This research aims to know anoverview of the factors that influence, how big internalfactors affect, as well as how much external factors affect.Thesis completion in students of the Building EngineeringEducation Study Program at during the Covid-19 pandemic.This research uses descriptive quantitative method. Theresearch instrument used was a questionnaire involvingstudents Building Engineering Education Study ProgramBatch 2016 as a population. Result research shows that thepercentage of internal factors is greater than the factorsexternal. The influence of internal factors on the completionof the thesis to obtain a percentage 53% while the influenceof external factors on the completion of the thesis is equalto 47%. In the internal factor the most influential is thedesire indicator completing the thesis on time in the aspectof motivation, while the interaction is in the guidanceprocess in the aspect of the guidance process is the mostindicator influence in external factors.